LARANGAN KAWIN KARENA PERTALIAN SESUSUAN DALAM PERSPEKTIF FIKIH DAN KOMPILASI HUKUM ISLAM - Rasyidin Imran (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Marriage due to interrelated relations in fiqh terminology is called radha'ah. all scholars agree (ijma ') for their prohibition. those who disagree are between the boundaries of the category of intervention (radha'ah), levels of susuance, length of intake, and trading of milk. The latter is interesting when giving birth to contemporary problems, such as the existence of ASI banks, ASI injection, ASI diverting.KMI does not cover contemporary issues as above, because historically the reference to KHI has been colored more by the works of Sunni Fiqh schools, especially Shafi'i Fiqh. and alternative answers are found in fiqh, namely the fiqh of the zhahiri school and j'afari. Both of these schools agree that this is not included in the category of radha'ah (sesusuan), so marriage is haram. Because what is called radhaah (sesusuan) is by sucking on the tits of a woman who is breastfeeding with her mouth.